The price of salt ebook Or carol. - Highsmith, Patricia (2015)
A chance encounter between two lonely women leads to a passionate romance in this lesbian cult classic. Therese, a struggling young sales clerk, and Carol, a homemaker in the midst of a bitter divorce, abandon their oppressive daily routines for the freedom of the open road, where their love can blossom. But their newly discovered bliss is shattered when Carol is forced to choose between her child and her lover. Author Patricia Highsmith is best known for her psychological thrillers Strangers on a Train and The Talented Mr. Ripley . Originally published in 1952 under a pseudonym, The Price of Salt was heralded as "the novel of a love society forbids." Highsmith's sensitive treatment of fully realized characters who defy stereotypes about homosexuality marks a departure from previous lesbian pulp fiction. Erotic, eloquent, and suspenseful, this story offers an honest look at the necessity of being true to one's nature.